Modelling of ostrich egg using Cubic Hermite Curve / Fatin Nadiah Hamdan ... [et al.] - Hamdan, Fatin Nadiah; Meor Ahmad, Nur Afiqah; Mohd Hariri, Nurul A’qilah; Othman, Suziana Aida; Ramli, Masnira (2019)
Cubic Hermite Curve is applied to calculate the volume of the ostrich eggs. Twelve different sizes of ostrich were used as samples to get the volume. Length, width and actual volume are the input measured to generate the calculated volume. Vernier caliper and measuring cylinder are used to get the measurement of the input. Archimedes Principal method has been used to measure an actual volume of eggs. In order to generate calculated volume, the best fitted curve of the ostrich eggs was obtained by using the best fitted point in Cubic Hermite Curve equation. Besides, another way to determine the best fitted curve is by comparing the relative error of the three different gradients between calculated volume and actual volume.